SHOULD THE METHODOLOGY OF THE IX PLENUM CIVIL CASE FOR THE DEFINITION OF MANIFEST NULLITY BE CONSIDERED AS A VICE IN ITS APPLICATION? - Huamán García, Elizabeth Rosmery (2022)
Some provisions of our Civil Code are clear regarding their content and others are somewhat vague and questionable. A regulation that generates controversy in terms of its concept and use is the one referring to the legal acts or business that has led the Supreme Judges to issue contradictory and erroneous sentences based on the outdated notion or out of context. The aim of this paper is to analyze the methodology used by the Supreme Court in the IX Civil Cassation Plenary for the argumentation of the scope that it has given to the notion of manifest nullity, as a cause of nullity that can be easily noticed in the same contract or through other evidence. It is extremely important to establish the methodological errors incurred by the Supreme Court when improperly using what is treated in the doctrine, laws and national and international jurisprudence, to later contrast its limitations and propose its correction, in a way that is useful to our legal system